(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
It is undisputed that taking work and extracting labour from a child, takes away their normal imagination power and talent destroy their creativity and energy. Such state of affairs deprives them from getting education, hindering their mental as well as physical growth on whom destiny of the nation depends at large. Study of International Labour Organizations and other agencies clearly indicates that large numbers of children are at risk due to job hazards in the tender age and childhood, which become curse on a civilized society. In the words of Mr. M.P. Joseph, the then National Programme Co-ordinator IPEC “the employment of child labour is an intolerable disrespect for human dignity and enormous waste of human resources. There is need for concerted multi-frontal action to combat this unbearable social evil.”International Organizations and the Constitution of India together played a vital role in combating the problems of children and child labour. But there are various general enactments touching the miseries and solutions of children and child labour at workplace or otherwise. It is expedient to have a look on such provisions relating to children and child labour which are directly or indirectly in operation to eradicate the issues and challenges in the way to protect children from exploitation.